INTRAPERSONAL CONFLICT FACTORS OF PRIMARY SCHOOL TEACHERS - Pantiuk, Mykola; Sadova, Iryna; Lozynska, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
An essential characteristic of pedagogical activity is its conflict potential. Such specific features as high social and normative expectations and significant overloading of roles in combination with individual psychological characteristics of teacher's personality lead to the emergence or exacerbation of various intrapersonal conflicts. Unsettled conflict usually becomes a constant source of discontent with yourself and the environment, causes a high level of anxiety, starts devastating processes of emotional burnout. Therefore, it is important to provide timely assistance to teachers in situations of intrapersonal conflicts.The purpose of the article is to highlight the results of empirical identification of intrapersonal conflict factors of primary school teachers. To achieve this goal it is necessary to solve the following tasks: 1) to investigate the factors of teachers conflict behaviour at the empirical level; 2) to determine the specifics and nature of the relationship between the level and characteristics of conflict and creativity, between the motivation of achievement and development of subjective qualities of a primary school teacher.Research tools: adapted methods of K.Thomas (N.Hrishyna) on the diagnosis of the style of behaviour in a conflict situation; methods of diagnosis of personality motivation for success (T.Ehlers); methods of studying frustration reactions (S.Rosenzweig); methods of diagnostics of interpersonal relations (L.Sobchyk); A.Rukavyshnikov’s methods for the definition of mental burnout; Drawing Apperceptive Test (DAT); methods of self-actualization A.Maslow adapted by Gozman, Kroz & Latinskaya. The total number of respondents - 32 primary school teachers of secondary schools in Drohobych, Lviv region.The analysis of the obtained results showed that: 1) there are specific characteristic connections between the level and features of conflict, creativity, between the motivation of achievement and development of subjective qualities of a person; 2) internal conflict as an interpersonal phenomenon is both a personal characteristic and a determinant of social interaction. It has been found that rivalry, low verbal creativity, lack of communicative competence in combination with extrapunitive type of reactions cause increased conflict. According to the results of the researches, a significant number of primary school teachers under study (32%) have increased intrapersonal conflict. Of course, this alarming indicator prevents the establishment of optimal pedagogical communication and provokes conflict among children of primary school age.